Building Students’ Moral Resilience Through Islamic Religious Education (PAI) As a Preventive Effort Against Online Gambling in Madrasah - Elfizar, Elfizar; Mulia, Muji; Safriadi, Safriadi; Realita, Realita (Published by Center for Research and Community Service (LP2M) in cooperation with the Postgraduate Program of UIN Ar-Raniry Banda Aceh, Aceh, Indonesia., 2025)
The advancement of digital technology has increased teenagers’ access to information and entertainment but also poses serious challenges to morality, such as the rise of online gambling among adolescents. This study analyzes the role of Islamic Religious Education (PAI) in developing students’ moral resilience to prevent online gambling behavior and examines preventive strategies implemented in madrasah. This qualitative research employed a case study at MTsN 1 Aceh Selatan, collecting data through in-depth interviews, participatory observation, and document analysis. Data were thematically analyzed using source and method triangulation to enhance validity. The findings reveal that PAI teachers actively integrate Islamic values, Quranic and Hadith principles, and current issues into the learning process. Furthermore, the madrasah applies collaborative policies such as parental involvement, supervision of gadget usage, and character development through religious activities. The integration of religious values in PAI learning and collaborative madrasah policies is proven effective in building students’ moral resilience and preventing involvement in online gambling. These findings contribute to the development of religious-based character education models relevant in the digital era and may serve as a practical reference for other schools in developing strategies to prevent online gambling among teenagers.